Bee diversity (Hymenoptera, Apoidea) in Araucaria forest in southern Brazil - Denise Monique Dubet da Silva Mouga; Paulo Nogueira-Neto; Manuel Warkentin; Vanessa Feretti; Enderlei Dec (Acta Biológica Catarinense, 2016)
The apifauna of an araucaria forest in southern Brazil was studied during 2001 – 2003, using entomological nets on flowering plants. A total of 2,749 individuals were sampled from five subfamilies and 93 species of bees. A total of 82 species with up to 10 individuals were sampled and 29 species had no distribution for Santa Catarina. Non-corbiculate Apidae and Halictidae species predominated as well as individuals of corbiculate Apidae and Halictidae. There was a decrease in species richness in cold seasons, being then sampled only Augochloropsis sp. 01, Augochloropsis sp. 10, Exomalopsis tomentosa, Neocorynura aenigma, Paroxystoglossa brachycera, Trigona spinipes and Apis mellifera. A bivoltine pattern was noticed, with a peak in May and in September-November, for richness and abundance. Ecological indexes over the months were different with and without A. mellifera. The bee accumulation curve remained in elevation until the end of sampling. The richness estimators indicated values of 142 and 175 species. The bee species were sampled on 125 species of plants of 40 famillies and the most visited were Asteraceae, Fabaceae/Solanaceae, Euphorbiaceae/Lamiaceae, Malvaceae/Rosaceae and Commelinaceae/Cucurbitaceae/ Liliaceae/Verbenaceae. A total of 48 species of plants characteristics of araucaria forests were sampled.